Comparative Analysis and Benchmarking of Water Supply Systems and Services in Central and Eastern Europe - Tomas Suchacek; Alexandru Aldea; Jedrzej Bylka; Ivana Marko; Ladislav Tuhovcak (Proceedings, 2018)
This paper deals with a comparative analysis and benchmarking of drinking water supply systems and water supply sector in the selected countries of Central and Eastern Europe. These include the Czech Republic, Poland, Romania, and Slovakia. The article provides an analysis of existing benchmarking systems in each country. Methods of supervision and control over the assessment and the functioning of the organizations responsible for the assessment and benchmarking of water utilities are also described. Comparative analysis for the selected performance indicators is carried out. The units, methods of data collection and processing were described.